An Empirical Analysis of Workload and Work Dicipline as Predictors of Employee Performance - Nia Meitisari; Nabilatul Syathirah; Muhammad Ichsan Hadjri; Tiara Anggita Qurilmi (Universitas Nahdlatul Ulama Sidoarjo, 2025)
This study aims to analyze the effect of workload and work discipline on employee performance at Mega Fashion Palembang. The population in this research consists of all employees of Mega Fashion Palembang, totaling 94 individuals. This study employs a non-probability sampling method with a saturated sampling technique. Data were collected through questionnaires, and the data analysis was conducted using multiple regression. The results indicate that workload (X1) has a negative and statistically significant effect on employee performance (Y). Meanwhile, work discipline (X2) has a positive and statistically significant effect on employee performance (Y). Furthermore, workload (X1) and work discipline (X2) simultaneously have a significant influence on the performance of employees at Mega Fashion Palembang.